Inorganic geochemical, mineralogical and methane sorption capacities of Paleozoic shale formations from Western Peninsular Malaysia: Implication of shale gas potential - Ibad, S.M. (Elsevier Ltd, 2022)
An experimental study comprising methane sorption capacity (MSC), inorganic geochemical and mineralogical analysis was conducted to assess the shale gas potential, depositional environments, and tectonic settings in the Western Peninsula (WP) Malaysia. Here, we report 146 shale samples from seven Paleozoic formations in WP Malaysia, divided into four groups based on their ages. The results indicate MSC ranging between 0.054 and 0.065, 0.034 and 0.109, 0.032 and 0.069 and 0.021 and 0.100 mmol/g rock for Silurian-Devonian (S-D), Devonian, Carboniferous, and Permian shales, respectively. By comparison, the MSC of the WP Malaysia shale is close to obtainable values for Longmaxi (China) and Barnett (USA) shales. Geochemical characterization reveals that the studied Paleozoic shales were deposited mainly in continental island arc and active continental margin (ACM) under a reducing marine depositional environment. Sr/Cu, Rb/Sr,Sr/Ba ratios, and C-values reveal warm, humid to hot arid paleoclimate for the S-D and Carboniferous shale samples, and warm, humid paleoclimate for the Devonian and Permian shales. The PIA, CIW, and CIA values indicate the source rocks have been subjected to moderate to strong chemical weathering. Al2O3/TiO2, Zr/TiO2, and LREE/HREE ratio, Eu anomalies, and the binary plot of Zr/Sc and Th/Sc denote that the shales from WP Malaysia are derived from intermediate to felsic igneous source rock. Mineralogical analysis reveals that S-D and Permian shales generally possess less clay and more siliceous minerals than the Devonian and Carboniferous shales. Comparatively, the mineral content of the Paleozoic shales is close to the mineralogy of Niutitang and Longmaxi shales. The geochemical analysis indicates that the pyrobitumen reflectance of Paleozoic shale samples is overmatured. Overall, based on the derived geological data and comparative analysis with hot gas shale reservoirs around the world, high, moderate and low shale gas potentials were obtained for the Devonian and Permian shales, S-D shales and Carboniferous shales in WP Malaysia, respectively. Â© 2022 Elsevier Ltd